Impacts of Television Serials on Tamil Rural Women: A Data Mining Case Study of Theni District (International Journal of Engineering and Computer Science, 2015)
Television, a medium invented for entertainment, has become burdens to today’s life. Instead of improving the knowledge of the people, now-a-days the serials dramas broadcast on the Indian television channels become nuisance for human life. The rural people of Tamilnadu are greatly affected by these television dramas. The researcher conducted a case study in Theni district of Tamilnadu to analyze the impacts of television serials on rural adults and women using data mining clustering techniques. Data were collected from the public by a set of questioner and it is processed using R tool – a statistical tool which is used for data mining analysis. Gender, Age and educational level based classification is performed to analyze the impact of television serials. It is found that the rural women, irrespective of age, educational qualification are greatly affected by these serial dramas and wasting their precious time on this television serials. This research bring an alarm that these serial dramas become a threat to the socio-cultural values of Tamilnadu.